2017
DOI: 10.1186/s12884-017-1249-0
|View full text |Cite
|
Sign up to set email alerts
|

The burden of nausea and vomiting during pregnancy: severe impacts on quality of life, daily life functioning and willingness to become pregnant again – results from a cross-sectional study

Abstract: BackgroundThough nausea and vomiting is very common during pregnancy, no studies have investigated the impact of this condition on the women’s daily lives in a Scandinavian population. The aim of this study was to describe the burden of nausea and vomiting during pregnancy (NVP) on global quality of life, daily life functioning and willingness to become pregnant again according to the severity of NVP symptoms.MethodsThis study is a cross-sectional population-based study conducted in Norway. Pregnant women and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
85
4
9

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(101 citation statements)
references
References 35 publications
3
85
4
9
Order By: Relevance
“…Most of the studies focused on NVP and HG found conflicting results with respect to the development of anxiety and depression disorders [7][8][9]. In addition to these conflicting results, some studies have been criticized for having limitations, including small sample size, lack of control group, lack of objective diagnostic criteria, and inappropriate study design [5,8,10,11]. Hence, the objective of this prospective case-control study was to determine the prevalence and severity of anxiety and depression disorders in patients with NVP using specifically designed and validated tools.…”
Section: Effect Of Nausea and Vomiting On Anxiety And Depression Levementioning
confidence: 99%
See 1 more Smart Citation
“…Most of the studies focused on NVP and HG found conflicting results with respect to the development of anxiety and depression disorders [7][8][9]. In addition to these conflicting results, some studies have been criticized for having limitations, including small sample size, lack of control group, lack of objective diagnostic criteria, and inappropriate study design [5,8,10,11]. Hence, the objective of this prospective case-control study was to determine the prevalence and severity of anxiety and depression disorders in patients with NVP using specifically designed and validated tools.…”
Section: Effect Of Nausea and Vomiting On Anxiety And Depression Levementioning
confidence: 99%
“…Pregnant women with severe nausea and vomiting may have hyperemesis gravidarum (HG), a separate entity from nausea and vomiting of pregnancy (NVP), which if left untreated may lead to increased maternal and fetal morbidity. HG is infrequent when compared with NVP and occurs in 0.3%-2% of all pregnancies [1,4,5]. The severity of complaints might vary from one pregnant woman to another and even between pregnancies of the same woman, which suggest the contribution of genetic, biological, and psychological factors.…”
Section: Introductionmentioning
confidence: 99%
“…Up to two thirds of women with hyperemesis are reported to have gestational transient thyrotoxicosis, although not necessitating treatment (54). Lastly, the condition may lead to significant psychological and emotional distress during as well as long after pregnancy (43,74).…”
Section: Short-termmentioning
confidence: 99%
“…¶ Net job creation effect: job creation (1.146)-job consumed by self for labor period (0.613)=0.533. (Heitmann et al, 2017;Lacasse et al, 2008). 그리고 임신부에게 스트레스와 우울감을 증가시킨다 (Yilmaz et al, 2016).…”
Section: 서 론mentioning
confidence: 99%